Sustained release of stromal cell–derived factor‐1 alpha from silk fibroin microfiber promotes urethral reconstruction in rabbits. Issue 8 (21st April 2020) - Liu, Yang; Huang, Li; Yuan, Wei; Zhang, Dongliang; Gu, Yubo; Huang, Jianwen; Murphy, Sean; Ali, Mohamed; Zhang, Yaopeng; Song, Lujie
Abstract: We developed a stromal cell–derived factor‐1 alpha (SDF‐1α)‐aligned silk fibroin (SF)/three‐dimensional porous bladder acellular matrix graft (3D‐BAMG) composite scaffold for long‐section ventral urethral regeneration and repair in vivo. SDF‐1α‐aligned SF microfiber/3D‐BAMG, aligned SF microfiber/3D‐BAMG, and nonaligned SF microfiber/3D‐BAMG scaffolds were prepared using electrostatic spinning and wet processing. Adipose‐derived stem cell (ADSC) and bone marrow stromal cell (BMSC) migration was assessed in the SDF‐1α‐loaded scaffolds. Sustained SDF‐1α release in vitro and vivo was analyzed using enzyme‐linked immunosorbent assay (ELISA) and western blotting, respectively. The scaffolds were used to repair a 1.5 × 1 cm 2 ventral urethral defect in male rabbits in vivo. General observation and retrograde urinary tract contrast assessment were used to examine urethral lumen patency and continuity at 1 and 3 months post‐surgery. Postoperative rehabilitation was evaluated using histological detection. The composite scaffolds sustained SDF‐1α release for over 16 days in vitro. SDF‐1α‐aligned SF nanofiber promoted regeneration of urethral mucosa, submucosal smooth muscles, and microvasculature, increased cellular proliferation, and reduced collagen deposition. SDF‐1α expression was increased in reconstructed urethra at 3 months post‐surgery in SDF‐1α‐aligned SF group. SDF‐1α‐aligned SF microfiber/3D‐BAMG scaffolds may be used to repair and reconstruct long urethral defects because they accelerate urethral regeneration.